Allergic airway diseases in childhood: An update. Issue 8 (December 2014) - Hofmaier, Stephanie
Abstract Complex multifactorial diseases such as allergic rhinitis and asthma are not only becoming an increasing burden to healthcare systems, but especially affect the life quality of children and families suffering from their allergic symptoms. Also physicians are challenged by the multifaceted diseases as their work involves not only the often difficult decisions on case‐adapted diagnostics, treatment, and monitoring, but also possible preventive measures. This review gives an outline of the latest scientific developments related to the etiology, diagnosis, and management of allergic airway diseases in childhood, as well as prenatal and early life risk factors and strategies for prevention.